Advances in Lipoprotein Research - Isbir, Turgay (IntechOpen, 2017)
Lipoproteins have key roles in human growth and development, along with promoting, preventing, and/or participating in the pathogenesis or in the treatment of various diseases. This book presents a systematic and comprehensive review about the structure and metabolism of lipoproteins, particularly highlighting the crucial role of those molecules in the body and considering the interest of some lipids in healthy and diseased conditions. This book aims to provide integrative approach to understand the lipoprotein metabolism. Distinguished international experts contributed six chapters about the genetic variations, plasma lipoprotein components, and molecular relationship of lipoproteins with cognition and obesity.